Commedia dell’arte and the Gate Theatre - Ian R. Walsh (Review of Irish Studies in Europe)
This essay reveals the centrality of commedia dell’arte in defining the Gate’s theatrical style in the first four decades of its existence. In its theatricality, as well as its emphasis on the international and the queer, Hilton Edwards and Micheál mac Liammóir found the commedia dell’arte to be an ideal theatrical precedent for their own ambitions and practice. Drawing on materials in the Gate Theatre Digital Archive, NUI Galway, newspaper archives, research by Christopher FitzSimons, David Clare and Nicola Morris and the books of Edwards and mac Liammóir this article charts the origins of their engagement with and conception of the commedia dell’arte and its manifestation in their writings and theatre productions. Building on the work of Eibhear Walshe and Richard Pine on mac Liammóir’s adoption of masks of identity, it is also argues that both Edwards and mac Liammóir assumed the masks of Harlequin and Pierrot, in their writing and performing in order to reveal and shape their queer identities. This examination confirms how embedded European theatrical practice was in the stagecraft of one of Ireland’s premiere theatres and in so doing allows for networks of international artistic influence to be traced in the development of contemporary Irish performance.